DZIAŁALNOŚĆ JOHNA BAGOTA GLUBBA – POLITYCZNE SKUTKI TOLERANCJI KULTUROWEJ - Wróblewski, Bartosz (Polityka i Społeczeństwo, 2020)
The contemporary western political discourse is dominated by the conviction of the equality of cultures. This conviction is treated as a recent accomplishment of the leftist liberal trend of western societies. The following text indicates that this conviction may in certain cases be invalid. The person who shattered this concept was John Bagot Glubb. This British officer serving the British Empire in the Middle East since 1921 was the chief commander of the Jordan army in the period between 1939 and 1956. J. B. Glubb was a conservative member of an old noble family from the south of England and at the same time he was passionate about the Arabic culture – in particular about the life of the Bedouin. In contrast to many contemporary supporters of political correctness, he did not depreciate his own culture, but he showed genuine recognition of many features of the Arabic culture. He spent his whole life working to bring the West and the Arabs closer. Now one may accuse J.B. Glubb of numerous political mistakes, e.g., typically British paternalism, but nonetheless his life indicates that it was possible for an activist representing the conservative trend in the European culture to be a proponent of bringing cultures together